2015
DOI: 10.1101/027383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Speciation driven by hybridization and chromosomal plasticity in a wild yeast

Abstract: Hybridization is recognized as a powerful mechanism of speciation and a driving force in generating biodiversity. However, only few multicellular species, limited to a handful of plants and animals, have been shown to fulfill all the criteria of homoploid hybrid speciation. This lack of evidence could lead to the misconception that speciation by hybridization has a limited role in eukaryotes, particularly in single-celled organisms. Laboratory experiments have revealed that fungi such as budding yeasts can rap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 49 publications
4
38
0
Order By: Relevance
“…Hybridization is now widely recognized to be an important evolutionary process which might play a crucial role in speciation (Gross and Rieseberg 2005;Mallet 2007;Schumer et al 2014;Taylor and Larson 2019). Hybridization followed by reproductive isolation has been reported to contribute to rapid speciation of yeast (Leducq et al 2016) and the same has been supposed to occur in some filamentous fungi (Kohn 2005;Gladieux et al 2014;Sillo et al 2019). Du et al (2012) reported the 85.2% of the species in the Esculenta Clade (including almost 90% of the Chinese species lineages) diversified and went through rapid speciation in East Asia since the middle Miocene, which might have contributed to the potential hybridization and gene transfer events detected in the Esculenta Clade.…”
Section: Conflicts Between Non-reproductive Genes (F1 and Igs) And Thmentioning
confidence: 99%
“…Hybridization is now widely recognized to be an important evolutionary process which might play a crucial role in speciation (Gross and Rieseberg 2005;Mallet 2007;Schumer et al 2014;Taylor and Larson 2019). Hybridization followed by reproductive isolation has been reported to contribute to rapid speciation of yeast (Leducq et al 2016) and the same has been supposed to occur in some filamentous fungi (Kohn 2005;Gladieux et al 2014;Sillo et al 2019). Du et al (2012) reported the 85.2% of the species in the Esculenta Clade (including almost 90% of the Chinese species lineages) diversified and went through rapid speciation in East Asia since the middle Miocene, which might have contributed to the potential hybridization and gene transfer events detected in the Esculenta Clade.…”
Section: Conflicts Between Non-reproductive Genes (F1 and Igs) And Thmentioning
confidence: 99%
“…In contrast there is an extensive literature describing diversity and quantitative genetics in the budding yeast Saccharomyces cerevisiae and its wild relative Saccharomyces paradoxus, and a range of related species (Peter & Schacherer, ). These include QTL studies (Bloom, Ehrenreich, Loo, Lite & Kruglyak, ; Fay, ; Liti & Louis, ; Märtens, Hallin, Warringer, Liti, & Parts, ; Swinnen, Thevelein, & Nevoigt, ), genome‐scale analysis of diversity (Liti, Carter, Moses, et al, ; Schacherer, Shapiro, Ruderfer, & Kruglyak, ) and analysis of diversity and evolution in the natural environment (Leducq et al, ; Robinson, Pinharanda, & Bensasson, ). In this review, I survey fission yeast diversity research, and I discuss what little is known about the origins and natural ecology of this species.…”
Section: Introductionmentioning
confidence: 99%
“…Population genomic studies have already added substantial depth and breadth to the knowledge of basic fungal biology, allowing researchers to address questions that were once intractable about the life history and evolution of reproductive systems. For example, fungi that have only been observed reproducing asexually show genomic evidence for sexual reproduction (Tsai et al., ; Stefanini et al., ); speciation through homoploid hybridization has been shown to occur rapidly, at least in yeast (Leducq et al., ); and Glomerales, arbuscular mycorrhizal fungi, have highly flexible levels of ploidy in the heterokaryotic cells within species (Wyss et al., ). Applying these methods to lichenized fungi holds great promise to rapidly advance knowledge of lichen population biology.…”
mentioning
confidence: 99%